Synthesis, Spatial Structure and Analgesic Activity of Sodium 3-Benzylaminocarbonyl-1-methyl-2,2-dioxo-1H-2λ6,1-benzothiazin-4-olate Solvates - Igor V. Ukrainets; Lidiya A. Petrushova; Svitlana V. Shishkina; Lina A. Grinevich; Galina Sim (MDPI AG, 2016)
In order to obtain and then test pharmocologically any possible conformers of the new feasible analgesic N-benzyl-4-hydroxy-1-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxamide, its 4-O-sodium salt was synthesized using two methods. X-ray diffraction study made possible to determine that, depending on the chosen synthesis conditions, the above-mentioned compound forms either monosolvate with methanol or monohydrate, where organic anion exists in the form of three different conformers. Pharmacological testing of the two known pseudo-enantiomeric forms of the original N-benzylamide and of the two solvates of its sodium salt was performed simultaneously under the same conditions and in equimolar doses. Comparison of the results obtained while studying the peculiarities of the synthesized compounds spatial structure and biological properties revealed an important structure-action relationship. In particular, it was shown that the intensity of analgesic effect of different conformational isomers of N-benzyl-4-hydroxy-1-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxamide may change considerably: while low active conformers are comparable with piroxicam, highly active conformers are more than twice as effective as meloxicam.